Digital Behavior Analysis and Decoding Marketing Merits of Top Indian Institutes - Agrawal, Mitalee (Tecno Scientifica Publishing, 2024)
The impact of social media on higher education institutions is extensive, making it a crucial focus for studying the role of social media marketing in education. In India, the National Institutional Ranking Framework (NIRF) plays a pivotal role in assessing the position of higher education institutes, categorized as public/private and technical/non-technical. NIRF 2022 ranked 1,350 institutes, considering parameters such as academics, research, innovation, financials, graduate outcomes, inclusivity, and perception. While perception holds a 10% weight, it significantly influences other primary parameters. Post-COVID and thanks to rapid digitalization, there has been a significant surge in social media usage by the youth of the country. Consequently, social media has emerged as a prime source of communication for educational institutes as well. This study focuses on analyzing